Analisis Risiko Investasi Saham Sektor Perbankan Syariah Menggunakan Perhitungan Value at Risk (VaR) dengan Model Simulasi Monte Carlo - Marlinda Marlinda (Seutia Hukamaa Cendekia, 2024)
Risk is a fact that investors must face in stock investment activities. Investors need risk management and estimation to avoid higher risks due to stock price fluctuations that are difficult to predict. Risk management is a system of supervision and protection to minimize acceptable risks. The risk of a stock can be measured using Value at Risk (VaR). VaR is an estimate of the maximum risk obtained by investors under normal market conditions, periods and certain levels of confidence. One of the methods used to determine VaR is Monte Carlo Simulation which includes the generation of random numbers. This method is considered the most powerful in estimating VaR. This study aims to estimate stock risk on single assets and portfolios at BRIS and BTPS for the period January 1, 2021 - December 31, 2023, using VaR calculation with Monte Carlo simulation. The secondary data used in this study is the daily closing stock price data of PT Bank Syariah Indonesia Tbk (BRIS) and PT Bank BTPN Syariah Tbk (BTPS) during the period January 1, 2021-31 December 2023. Based on the results of the test analysis, it shows that on a single asset, PT Bank BTPN Syariah Tbk (BTPS) has a VaR level of IDR 20,014,498 higher than the VaR level of PT Bank Syariah Indonesia Tbk (BRIS) of IDR 19,947,342. In the calculation of the portfolio with the weight of BRIS = 50% and BTPS = 50% shares shows a loss of Rp15,529,484. The VaR value is lower than the VaR value of each asset, it can be concluded that the diversification effect can minimize the risk of stock investment.